1998
DOI: 10.1136/ip.4.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bicycle injury, head injury, and helmet use among children in British Columbia: a five year descriptive study

Abstract: Conclusion-The data indicate the need to control injuries by using helmets. A decrease in the number of head injuries and their severity is expected when bicycle helmet use becomes law in British Columbia. (Injury Prevention 1998;4:122-125)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 23 publications
4
33
0
2
Order By: Relevance
“…32 Our findings regarding bicycle-related amputations are consistent with multiple studies indicating that school-aged children are at the highest risk for such injuries. [47][48][49][50] Our data also showed that bicyclerelated amputations are more often complete than amputations associated with any other product. The majority of these injuries were to fingers, with some toe injuries.…”
Section: Discussionmentioning
confidence: 66%
“…32 Our findings regarding bicycle-related amputations are consistent with multiple studies indicating that school-aged children are at the highest risk for such injuries. [47][48][49][50] Our data also showed that bicyclerelated amputations are more often complete than amputations associated with any other product. The majority of these injuries were to fingers, with some toe injuries.…”
Section: Discussionmentioning
confidence: 66%
“…Helmet use significantly reduced risk of head injury (OR 0.15, 0.07-0.29) and brain injury (OR 0.12, 0.04-0.40) Wasserman (1990) [ [57] Bicycling Helmet Severe head injury Decrease in severe head injury rates over years of increasing helmet use Finvers (1996) [69] Bicycling Helmet Severe head injury Significantly increased risk of severe head injury without helmet (OR 3.12, 1.13-8.75) Linn (1998) [61] Bicycling [44] Ski and Snowboard Helmet Head injury Helmet use significantly reduced risk of head injury (p < 0.05) Rughani (2011) [45] Ski and Snowboard Helmet Skull fractures Helmet use associated with lower incidence of skull (p = 0.009) and craniofacial (p = 0.03) fractures Delaney (2008) [84] Soccer Headgear Concussion Increased concussion rate with not wearing headgear (RR 2.65, p = 0.001) Kraus (1970) [24] Hockey Helmet Head injury Helmet use significantly reduced risk of head injury (p = 0.03) Bond (1995) [55] Horseback riding Helmet Head injury Significantly more severe head injuries without helmet use and higher rate of hospitalization Brandenburg and Archer (2002) [54] Rodeo Helmet Head injury Helmet use significantly reduced risk of head injury (IRR 0.43, 0.26-1.02)…”
Section: Baseball and Cricketmentioning
confidence: 98%
“…Powell and Tranz estimated the rate of head trauma presenting to the Emergency Department among American children aged 1-14 years to be 7.3 per 10 000 children (3). Among children presenting to the Emergency Department following a cycling injury, 22-40% had sustained a head injury and the majority of children were not wearing a helmet (4)(5)(6). Approximately 40% of children who were admitted to the hospital or died owing to a cycling-related injury had experienced head trauma (7).…”
Section: Description Of the Conditionmentioning
confidence: 98%